Intoleransi dan Sektarianisme Keagamaan: Sebuah Survey Literatur - Zuly Qodir (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2017)
The study in this paper provides an explanation about the issue of sectarianism and religious intolerance occurring in Indonesia especially and someother countries. There are several factors that influence such as mentalhealth factors, economic and political factors other than religious commitments that encourage a person to perform jihad actions that are interpretedas "war" by violence. There is a lot of field data explaining the occurrence ofviolent and intolerant practices in Indonesia. The study in this paper is basedon literature review either in the form of books, research or survey conducted by several independent institutions in Indonesia.